Rivaroxaban as A Therapy in Cerebral Venous Thrombosis (CVT): A Systematic Review - Maisan Nafi'; Agnes Ardelia Permatasari; Adrianus Setyawan Adhitama (Magna Neurologica, 2025)
Background: Cerebral venous thrombosis (CVT) can be fatal if untreated. The European Stroke Organization recommends Low Molecular Weight Heparin in the acute phase and oral anticoagulants (VKA) for 3-12 months post-acute to prevent recurrence. Rivaroxaban, a Direct Oral Anticoagulant (DOAC) inhibiting factor Xa, is associated with reduced risks of fatal bleeding and intracranial hematoma. This systematic review aims to evaluate the efficacy and safety of Rivaroxaban therapy in CVT patients. Objective: To evaluate the efficacy and safety of Rivaroxaban therapy in patients with cerebral venous thrombosis (CVT), particularly post-acute phase, through a systematic review of relevant studies. Methods: Our review based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines with an electronic search using PubMed, Cochrane, Sage, Embase, and Ebsco published between 2012 and 2022. This study included patient with CVT above 18 years old, confirmed by radiographic examination. Results: From 339 studies we found, 6 studies were included with 113 participants who completed the research program. Major bleeding was 2.26% (n=3).Venous thromboembolism was 1.7% (n=2). Recurrent CVT was 1.7% (n=2). Score of mRS 0-1 was 76% (n=86), mRS score 2 was 2.6% (n=3) while 21 subject in a study were evaluated with NIHSS. Death was found 1.7% (n=2) which caused still unknown. Recanalization in 6-12 months both partial and complete was reported 66.3% (n=75), no recanalization was 1.7% (n=2), no recanalization evaluation was found 30.9% (n=35). Conclusion: Rivaroxaban appeared to be safe and has good efficacy as a therapy in patient with CVT after acute phase.